2020
DOI: 10.3389/fonc.2020.01638
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Decision Rules and Risk Assessment Model for Preoperative Prediction of Lymph Node Metastasis in Gastric Cancer

Abstract: Background: Preoperative accurate prediction of lymph node status is especially important for the formulation of treatment plans for patients with gastric cancer (GC). The purpose of this study was to establish decision rules and a risk assessment model for lymph node metastasis (LNM) in GC using preoperative indicators. Methods: The clinical data of 554 patients who underwent gastrectomy with D2 lymphadenectomy were collected. A 1:1 propensity score matching (PSM) system was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 81 publications
(83 reference statements)
3
19
0
Order By: Relevance
“…After consulting a large number of literature, we consider the easily and simply tumor markers (CA19-9 and CEA) as major clinical risk factors. Existing studies have shown that CEA level was a significant predictive marker for the N stage in patients with GC [27,28]. In our study, the results also suggested that CEA level was an important predictive factor besides the PET Rad-score according to AIC.…”
Section: Discussionsupporting
confidence: 81%
“…After consulting a large number of literature, we consider the easily and simply tumor markers (CA19-9 and CEA) as major clinical risk factors. Existing studies have shown that CEA level was a significant predictive marker for the N stage in patients with GC [27,28]. In our study, the results also suggested that CEA level was an important predictive factor besides the PET Rad-score according to AIC.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, long-term alcohol consumption can lead to violation of the protein synthesis function of liver, followed by the development of lower nutritional levels. This study also found that the degree of tumor differentiation and depth of infiltration were independent risk factors for LNM, which showed great similarity with the results of other studies (34)(35)(36).…”
Section: B Asupporting
confidence: 89%
“…In the clinical-radiomics nomogram model for LNM prediction in CRC developed by Li et al (2020) , CA19-9 has greater weight of feature coefficients than CEA. Huang et al (2020) have also revealed that CA19-9 has higher AUC than CEA for LNM assessment in gastric cancer. These findings parallel the results displayed in Tables S4 of our study.…”
Section: Discussionmentioning
confidence: 93%